2016
DOI: 10.1016/j.dhjo.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Systematic overview of economic evaluations of health-related rehabilitation

Abstract: Although the available evidence is often described as limited, inconsistent or inconclusive, some rehabilitation interventions were cost-effective or showed cost-saving in a variety of disability conditions. Available evidence comes predominantly from high income countries, therefore economic evaluations of health-related rehabilitation are urgently required in less resourced settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
58
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 80 publications
0
58
0
5
Order By: Relevance
“…The socioeconomic status and social support of patients with disability should be thought as the major factors affecting long‐term outcome and life span 1, 16. Patients who survive a stroke may be frustrated to manage the new experience of disability or impairment by themselves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The socioeconomic status and social support of patients with disability should be thought as the major factors affecting long‐term outcome and life span 1, 16. Patients who survive a stroke may be frustrated to manage the new experience of disability or impairment by themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke usually causes disability or restricts daily activities, thereby resulting in long‐term reduction in quality of life for those who have had one. Stroke is listed as the most common cause of disability in adults worldwide 1, 2, 3. In Western developed countries, poststroke patients might exhibit high intolerance of their disability, and several studies have revealed notably higher rates of suicide ideation, suicide attempts, and completed suicides in poststroke patients than in the general population 4, 5, 6.…”
mentioning
confidence: 99%
“…Many countries including the Nordic countries and UK have over decades experienced increasing numbers of people leaving the labor market because of reduced workability (MacAllister et al, 2015). The evidence of what are cost-effective methods of rehabilitation is also rather limited (Howard-Wilsher, 2016) and the health care structure for long term rehabilitation demands close collaboration between primary care, hospitals, municipalities, employers etc. But many health care reforms, marketization and new economic incentives have promoted a fragmentation rather than stronger collaboration within health care systems.…”
Section: The Policy Entry Points To Tackle the Health Dividementioning
confidence: 99%
“…The role that rehabilitation plays in maximising the impact of other health services — such as surgical interventions, trauma care and management of noncommunicable diseases — and its potential for significant cost savings are also frequently misunderstood and underestimated [12]. For example, rehabilitation has been found to be beneficial in reducing length-of-stay in hospitals and decreasing re-admissions, thus mitigating the negative social and health risks associated with prolonged hospitalizations.…”
mentioning
confidence: 99%